Influence of UDP‐Glucuronosyltransferase Polymorphisms on Stable Warfarin Doses in Patients with Mechanical Cardiac Valves. Issue 6 (December 2015) - An, Sook Hee; Chang, Byung Chul; Lee, Kyung Eun; Gwak, Hye Sun
Summary: Aim: This study aimed to evaluate the effect of uridine diphosphate (UDP)‐glucuronosyltransferase (UGT) polymorphisms on warfarin dosing requirements in patients with mechanical cardiac valves. Methods: A total of 191 patients with stable warfarin doses from the EAST Group of Warfarin were included in this study. The influence of genetic polymorphisms on stable warfarin doses was investigated by genotyping 6 single nucleotide polymorphisms (SNPs): vitamin K epoxide reductase complex 1 (VKORC1) rs9934438, cytochrome P450 (CYP) 2C9 rs1057910, CYP4F2 rs2108622, and UGT1A1 (rs887829, rs4148323, and rs4124874). An additional subgroup analysis was carried out using patients with wild‐type homozygote carriers of CYP2C9. Results: One UGT1A1 SNP of rs887829 (C>T) exhibited significant association with stable warfarin doses in the study population and subgroup. Patients with the T allele in UGT1A1 rs887829 (CT or TT) required higher doses than those with the CC genotype in the study population (6.3 ± 2.4 mg vs. 5.2 ± 1.6 mg, P  = 0.003). Similarly, in the subpopulation of AA carriers in the CYP2C9 gene, patients with the T allele required significantly higher doses of warfarin than those with other genotypes of rs887829 (6.5 ± 2.4 vs. 5.3 ± 1.5 mg, P  = 0.002). Approximately 45.1% of overall interindividual variability in warfarin dose requirement was explained by the multivariate regression model. VKORC1, CYP2C9, UGT1A1 rs887829, age, and CYP4F2 accounted for 28.2%, 6.6%, 5.5%, 3.0%, and 1.8% of the variability, respectively. Conclusion: Our results suggest that UGT1A1 could be a determinant of stable warfarin doses.